Philodemus and poetry : poetic theory and practice in Lucretius, Philodemus, and Horace - Obbink, Dirk (OUP E-Books., 1995)
Building on recent advances in the reconstruction of the charred papyri of Philodemus of Gadara (ca. 110-40 B.C.) excavated from the Villa of the Papyri at Herculaneum, this volume presents eleven new chapters in the history of literary criticism in antiquity. The essays, written by noted scholars, treat the papyrus texts of Philodemus' treatises on poetry and the related subjects of rhetoric and music, establishing links with his Roman contemporaries Lucretius, Catullus, Horace, and Vergil. The study offers a critical survey of current trends and developments in recent scholarship on Philodemus in particular and Hellenistic literary theory in general.